Cadet Caroline Kennedy, LA '06, receives the battalion and attends morning classes and exercises at the MIT ROTC offices. Photo 048 - Ko, Melody (Tufts Archival Research Center, 2008)
Cadet Caroline Kennedy, LA '06, receives the battalion and attends morning classes and exercises at the MIT ROTC offices.